REFINING OF CALOPHYLLUM OIL AND ITS APPLICATION AS BIOFUEL - Ika Amalia Kartika, Syelly Fathiayah, Desrial dan Yohanes Ari Purwanto (Jurnal Teknologi Industri Pertanian, 2010)
BSTRACT  The objective of this research was to study the refining of calophyllum oils and its characterization as a biofuel substitute for diesel fuel.  The dosage of phosphoric acid solution of 20% (0.2 - 0.3%) and the NaOH concentration (14-18 °Be) were examined to determine the best performance of the refining process and the quality of refined calophyllum oil. The block experimental design and ANOVA (F-test at α = 0.05) were applied to study the effects of dosage of phosphoric acid solution of 20% and NaOH concentration on oil loss and its quality. Generally, the block and the NaOH concentration affected significantly the oil loss and the quality of refined oil. A significant increase of oil loss was observed as increasing of NaOH concentration. The dosage of phosphoric acid solution did not affect the oil loss and the quality of refined oil.  However, an increase of the dosage of phosphoric acid solution tended to decrease the ash content and viscosity of refined oil, but did not affect any other parameters. The best treatment for calophyllum oil refining was obtained on the block 1, and the phosphoric acid solution dosage of 0.2% and NaOH concentration of 18 °Be. This treatment gave the oil loss of 36.8%, the acid value of 0.23 mg NaOH/g, the saponification value of 174.93 mg KOH/g, the peroxide value of 7 meq/kg, the ash content of 0.003% and the viscosity of 32.5 cP. The quality of refined calophyllum oil under this optimum condition fulfilled the Biofuel Standard. Keywords: calophyllum oil, degumming, neutralization, biofuel